A Critical Examination of Inter-temporal Spatial Poverty Trends in Bangladesh: The Case of the East–West Divide. Issue 1 (March 2018) - Rahman, Shadlee
This article examines the nature of spatial dimensions of poverty in Bangladesh by undertaking an in-depth investigation of inter-temporal divergence and convergence in poverty levels. Based on the estimations of Alkire–Foster Multidimensional Poverty Index (A–F MPI) for selected years, the article compares trends in broader dimensions of spatial poverty in Bangladesh with income poverty trends available for corresponding periods. The article scrutinizes the validity of the so-called 'East–West divide' in view of poverty levels in Bangladesh. The results evince a number of interesting insights. First, trends of income poverty in Bangladesh are not aligned with those of multidimensional poverty. Second, the levels of inter-temporal poverty as per MPI are relatively higher for the rural–urban divide and also at sub-national (division) levels. Third, inter-temporal trends of divergence–convergence in terms of income poverty relating to the East–West divide do not match corresponding movements in MPI. It is argued that while income poverty dimensions remain important, policymakers should pay more attention to broader issues of deprivations to address challenges of poverty in Bangladesh. Therefore, addressing causes of deprivations as captured in MPIs will help achieve balanced spatial development, accelerated poverty reduction and lower income inequality in Bangladesh. JEL: R11, R12, I32, C22